Case Report and Literature Review: Unusual Presentation of Genitourinary & Gastrointestinal Metastases from Invasive Lobular Carcinoma of the Breast - Al-Musalhi, Khadija; Al-Qassabi, Badryia; Al-Ajmi, Radiya; Al-Aghbari, Suad (International Journal of Innovative Research in Medical Science, 2020)
Unlike invasive ductal carcinoma, lobular carcinoma exhibits a distinct metastatic pattern. It is likely to spread to gynecological organs, peritoneum, retroperitoneum, brain and gastrointestinal tract in comparison to ductal carcinoma, which spreads to liver, lung, and brain tissues. The diagnosis becomes more unlikely on the rare occasion when it represents the first manifestation of breast cancer. It is important to differentiate the metastasis from primary carcinoma of genital or GI tract as the management substantially differs. In this report; we present a 47 years-old female patient who presented with gynecological organs & gastrointestinal tract involvement as initial presentation and literature review done for these unusual sites of metastasis.